(untitled) (International Journal of Engineering and Computer Science, 2017)
Matrix converters are frequency converters which do not contain a direct current link circuit with passive components, unlike conventional frequency converters. Thus, matrix converters may provide a solution for applications where large passive components are not allowed, or a purely semiconductor-based solution provides an economically more efficient result than conventional frequency converters. The matrix converter (MC) is an alternative AC-AC power converter by connecting the direct input to output phases through bidirectional switches and without using any dc-link or energy storing element, therefore, is called an all-silicon converter. Two topologies of matrix converter are established such as linear topology and the indirect topology. This paper is devoting to presents the topology of the Very Sparse Matrix Converter (VSMC). The article is focused on Easy Commutation Space Vector Modulation (ECSVM) modelling applied to the very sparse matrix converter (VSMC).